1923 N.H. Laws 138, § 8 - (:unkn) unknown (My University, 1923)
No person shall sell, deliver, or otherwise transfer a pistol or revolver to a person who is an unnaturalized foreign-born person or has been convicted of a felony against the person§ property of another, except upon delivery of a written permit to purchase, signed by the selectmen of the town or the mayor or chief of police of the city
Keywords: TRANSFER - DANGEROUS PERSONS